ChemInform Abstract: "On‐Water" Synthesis of 3‐Substituted Indoles via Knoevenagel/Michael Addition Sequence Catalyzed by Cu Doped ZnS NPs. Issue 7 (18th February 2014) - Dandia, Anshu; Gupta, Shyam L.; Parewa, Vijay; Sharma, Amit; Rathore, Kuldeep S.; Sharma, Amit
Abstract Cu doped ZnS nanoparticles (NPs) represent a green catalyst for a one‐pot rapid synthesis of 3‐substituted indole derivatives via Knoevenagel/Michael addition reaction in aqueous medium.